Effect of Waterjet Machining Parameters on Cut Quality of Polymeric Composite Materials Based on Biological Reinforcement in Form of Cotton Post-harvest Line Residues - Müller, Miroslav; Kolář, Viktor; Valášek, Petr (Manufacturing Technology Journal, 2019)
Composite materials are prospective materials. An intensive research on biological reinforced composite materials has taken place in recent years. The paper deals with utilization of just this biological filler in an area of the composite materials based on a synthetic laminating resin. A microparticle and short-fibre filler based on cotton post-harvest line residues was used within the research. Many research studies devote to an evaluation of mechanical properties and an interaction of the filler and the matrix. Also a production of a final product is an integral part of the composite material development, namely in terms of a practical application. The research focused on an essential production part, namely machining by means of a water jet technology and an optimization of the cutting process based on an evaluation of a traverse speed and a cut quality. The research results proved that it was suitable to use the abrasive water jet technology for the cut uniformity (the kerf taper angle) and a deformation elimination of outlet part of the water jet from the composite material. In case of using the water jet technology without abrasive it is suitable to use lower values of the traverse speed, ca. 250 mm/min.
Keywords: composites; biological filler; prospective technology; water jet